2021
DOI: 10.1016/j.bbi.2020.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain correlates of serum and epigenetic markers of inflammation in major depressive disorder

Abstract: Highlights First study of both serum and DNAm CRP associations with depression/neuroimaging. Serum CRP is associated with somatic symptoms and reduced entorhinal cortex thickness. DNAm CRP is associated with widespread reductions in white matter integrity. Evidence for central effects of peripheral inflammation from serum and DNAm markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
63
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 78 publications
6
63
1
Order By: Relevance
“…A large number of literature reports indicated that there was a deterministic relation between higher CRP level, change in brain structure, and depression (D'Mello & Swain, 2017; Felger et al., 2020; Kelly et al., 2019; Ng et al., 2018; Vulser et al., 2015), still the relationship between peripheral inflammation, brain structure, and depression remains unclear. A recent work showed that DNA methylation of CRP was significantly associated with reduced global gray matter/cortical volume and widespread reductions in integrity of 16/24 white matter tracts, the methylation‐based measures showed stronger associations with imaging metrics than serum‐based CRP measures, and these findings provide evidence for central effects of peripheral inflammation from both serological and epigenetic markers of inflammation, including in brain regions previously implicated in depression (Green et al., 2020). A review demonstrated that the early life adversity–perinatal depressive risk model, as we have proposed, invokes epigenetic embedding as a key pathway that promotes a pro‐inflammatory phenotype (higher levels of pro‐inflammatory cytokines and lower levels of oxytocin), which, in turn, shapes maternal stress reactivity, mood, and behavior (Garfield et al., 2015).…”
Section: Discussionmentioning
confidence: 92%
“…A large number of literature reports indicated that there was a deterministic relation between higher CRP level, change in brain structure, and depression (D'Mello & Swain, 2017; Felger et al., 2020; Kelly et al., 2019; Ng et al., 2018; Vulser et al., 2015), still the relationship between peripheral inflammation, brain structure, and depression remains unclear. A recent work showed that DNA methylation of CRP was significantly associated with reduced global gray matter/cortical volume and widespread reductions in integrity of 16/24 white matter tracts, the methylation‐based measures showed stronger associations with imaging metrics than serum‐based CRP measures, and these findings provide evidence for central effects of peripheral inflammation from both serological and epigenetic markers of inflammation, including in brain regions previously implicated in depression (Green et al., 2020). A review demonstrated that the early life adversity–perinatal depressive risk model, as we have proposed, invokes epigenetic embedding as a key pathway that promotes a pro‐inflammatory phenotype (higher levels of pro‐inflammatory cytokines and lower levels of oxytocin), which, in turn, shapes maternal stress reactivity, mood, and behavior (Garfield et al., 2015).…”
Section: Discussionmentioning
confidence: 92%
“…Third, there are potential factors such as a genetic predisposition or the gut microbiome mediating or moderating the relationship between inflammation and neural-circuit dysfunction in depression. 124 125 For example, a recent study by Green et al 126 found that the DNA methylation score of the CRP gene was associated with a reduction in global gray matter/cortical volumes and damaged integrity of the white matter in widespread tracts in patients with MDD, whereas no significant association was found between the serum CRP level and structural changes in the brain. Future studies should take these factors into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, changes in brain structure [11,12], gastrointestinal factors [13,14], oxidative stress [15], and endocannabinoid system components [16] have also been implicated in depression [17]. In addition, correlation studies for the aforementioned biomarkers such as inflammatory factors and brain structural changes also have been conducted in depression [18,19]. Family, twin, and adoption studies suggest that genetic factors account for 30-40% of the variance in depression risk [20], but early genome-wide association studies (GWASs) failed to identify genetic variants strongly associated with depression, suggesting that genetic susceptibility is mediated by heterogeneous combinations of risk alleles [21][22][23].…”
Section: Introductionmentioning
confidence: 99%